A Short History of the B-Cell-Associated Surface Molecule CD40 - Clark, Edward A. (Frontiers in Immunology, 2014)
This perspective traces developments using monoclonal antibody technology that led to the discovery of CD40, a receptor that on B cells mediates “T cell help” and on dendritic cells helps to program CD8 T cell responses. I discuss some things that we got right during the path of discovery and some things we missed. Immunotherapies that block or stimulate the CD40 pathway hold great promise for treatment of autoimmune diseases and cancers.